2021
DOI: 10.1021/acs.inorgchem.1c01087
|View full text |Cite
|
Sign up to set email alerts
|

Pressure-Induced Electronic and Structural Transition in Nodal-Line Semimetal ZrSiSe

Abstract: The nodal-line semimetals have recently gained attention as a promising material due to their exotic electronic structure and properties. Here, we investigated the structural evolution and physical properties of nodal-line semimetal ZrSiSe under pressure via experiments and theoretical calculations. An isostructural electronic transition is observed at ∼6 GPa. Upon further compression, the original tetragonal phase starts to transform into an orthorhombic phase at ∼13 GPa and the two phases coexist until the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Furthermore, the positions of 2D SDP can be modified by applying uniaxial strain or introducing vacancies . Multiple experimental and theoretical studies have observed the pressure-induced transitions in bulk compounds ZrSiX (where X can be elements like S, Se, or Te). The theoretical insights derived from first-principles calculations of HfGeTe have shed light on a sequence of pressure-induced transitions associated with 2D SDP distributed across various Brillouin zone positions in HfGeTe . This perceptive theoretical prognosis served as a robust catalyst for our extensive investigations into pressure-induced topological transitions within HfGeTe compounds through synchrotron X-ray diffraction, Raman scattering, and electrical transport measurements.…”
Section: Introductionmentioning
confidence: 96%
“…Furthermore, the positions of 2D SDP can be modified by applying uniaxial strain or introducing vacancies . Multiple experimental and theoretical studies have observed the pressure-induced transitions in bulk compounds ZrSiX (where X can be elements like S, Se, or Te). The theoretical insights derived from first-principles calculations of HfGeTe have shed light on a sequence of pressure-induced transitions associated with 2D SDP distributed across various Brillouin zone positions in HfGeTe . This perceptive theoretical prognosis served as a robust catalyst for our extensive investigations into pressure-induced topological transitions within HfGeTe compounds through synchrotron X-ray diffraction, Raman scattering, and electrical transport measurements.…”
Section: Introductionmentioning
confidence: 96%
“…Among the reported nodal-line semimetals, the ZrSiX family of materials has attracted significant attention due to the large energy window of the linear band dispersion in certain regions of the Brillouin zone . The band structures of these materials have been extensively investigated through theoretical calculations and angle-resolved photoemission spectroscopy (ARPES) measurements. , While the physical properties of typical type-I nodal-line semimetals have been studied using various transport and optical measurements, ,,, the band structure of ZrSiX near the Fermi energy in the Z-R range is predicted to exhibit the shape of a type-II nodal line, especially in the case of ZrSiSe …”
mentioning
confidence: 99%